2015
DOI: 10.1016/j.jelekin.2014.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Rigid and Elastic taping changes scapular kinematics and pain in subjects with shoulder impingement syndrome; an experimental study

Abstract: Background: Rigid and elastic scapular taping is used in physical rehabilitation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
6
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 49 publications
4
28
6
2
Order By: Relevance
“…subjects (Hsu et al, 2009;Lin et al, 2011;Shaheen et al, 2014;Van Herzeele et al, 2013). It has been suggested that these techniques can be helpful for shoulder injuries prevention and rehabilitation in overhead athletes (Hsu et al, 2009;Van Herzeele et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…subjects (Hsu et al, 2009;Lin et al, 2011;Shaheen et al, 2014;Van Herzeele et al, 2013). It has been suggested that these techniques can be helpful for shoulder injuries prevention and rehabilitation in overhead athletes (Hsu et al, 2009;Van Herzeele et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Suggesting the use of KT during sports or during physiotherapy rehabilitation in order take advantage of its immediate effects (27,28) . It is also reported the improved function provided by KT, because it does not restrict movement, giving more functionality (25,28,29) . Adapting the placement protocol, the researchers found that in the short term there is reduction of pain levels after the first week of intervention with KT in night pain, rest and activity scores (12) .…”
Section: Discussionmentioning
confidence: 98%
“…The KT protocol was already used in an identified or adapted way in other studies, however the effects on myoelectric activity in the shoulder were not evaluated, only the level of pain in different situations (12,13,25,26) . Using the same protocol evaluating pain level, the investigators studied the influence of KT on pain and disability in individuals diagnosed with SIS or rotator cuff tendonitis in the abduction, flexion, elevation movements in the plane of the scapula during a period of 6 days, performing evaluations on the 1st, 3rd and 6th day (13) .…”
Section: Discussionmentioning
confidence: 99%
“…Some specific elastic-taping techniques have become increasingly popular as clinicians try to solve a variety of musculoskeletal problems. Whereas the underlying mechanisms of taping are still unclear, researchers 21 have proposed that taping works by offering constant proprioceptive feedback or providing alignment correction during dynamic movements. Hsu et al 19 investigated the immediate effects of elastic taping on scapular kinematics, muscle strength, and electromyographic activity in baseball players with shoulder impingement.…”
Section: Discussionmentioning
confidence: 99%
“…15 Clinicians often manage SIS with various treatment techniques to address the strength deficits and altered pattern of scapular kinematics that lead to injury and are modifiable characteristics to improve patient outcomes, such as reducing pain and decreasing shoulder dysfunction. These techniques include, but are not limited to, posterior shoulder stretching for capsular abnormalities 16,17 ; scapular bracing to correct poor posture 18 ; taping that was claimed to correct aberrant kinematic patterns due to poor rotator cuff or scapular muscle function [19][20][21] ; thoracic spine manipulation to readjust the alignment of thoracic vertebrae where important scapular muscles are attached, modify costovertebral mobility, or possibly enhance neuromuscular control of scapulothoracic muscles [22][23][24][25] ; rotator cuff and other scapular muscle strengthening 8,16,[26][27][28][29] to stabilize or position the scapula properly 30 during dynamic shoulder movement; neuromuscular reeducation for coordinated activation of scapular muscles during shoulder movement 27,29 ; and manual therapy, such as joint mobilization to restore proper joint mobility. 31,32 The variation in intervention approaches is directly related to various views on the mechanism leading to impingement.…”
mentioning
confidence: 99%